СТРАТЕГІЯ ФОРМУВАННЯ КОГНІТИВНИХ СМИСЛІВ ЯК ФАКТОР ПРОФЕСІЙНОЇ ПІДГОТОВКИ ВЧИТЕЛЯ МИСТЕЦЬКИХ ДИСЦИПЛІН (Педагогіка вищої та середньої школи, 2022)
In article processes of an intensification of vocational training of the teacher of art in a context of modem strategy of training are considered It is accented oft expediency of comprehension of value of strategy of fomiation cognitive senses a universal principle of cognitive activity; the principles classified to an operational attribute are allocated; groups of these principles are considered in quality constrm strategy cognitive development of the person.